Multi-level influences on increased overdose risk behaviors during the COVID-19 pandemic among people who use drugs in Rhode Island: a qualitative investigation - Lisa Frueh; Alexandra B. Collins; Roxxanne Newman; Nancy P. Barnett; Josiah D. Rich; Melissa A. Clark; Brandon D. L. Marshall; Alexandria Macmadu (BMC, 2023)
Abstract Background The ongoing COVID-19 pandemic has disproportionately affected structurally vulnerable populations including people who use drugs (PWUD). Increased overdose risk behaviors among PWUD during the pandemic have been documented, with research underscoring the role of influencing factors such as isolation and job loss in these behaviors. Here, we use qualitative methods to examine the impact of the COVID-19 pandemic and pandemic-related response measures on drug use behaviors in a sample of PWUD in Rhode Island. Using a social-ecological framework, we highlight the nested, interactive levels of the pandemic's influence on increased overdose risk behaviors. Methods From July to October 2021, semi-structured interviews were conducted with 18 PWUD who self-reported any increase in behaviors associated with overdose risk (e.g., increased use, change in drug type and/or more solitary drug use) relative to before the pandemic. Thematic analysis was conducted using a codebook with salient themes identified from interview guides and those that emerged through close reading of transcribed interviews. Guided by a social-ecological framework, themes were grouped into individual, network, institutional, and policy-level influences of the pandemic on drug use behaviors. Results Individual-level influences on increased overdose risk behaviors included self-reported anxiety and depression, isolation and loneliness, and boredom. Network-level influences included changes in local drug supply and changes in social network composition specific to housing. At the institutional level, drug use patterns were influenced by reduced access to harm reduction or treatment services. At the policy level, increased overdose risk behaviors were related to financial changes, job loss, and business closures. All participants identified factors influencing overdose risk behaviors that corresponded to several nested social-ecological levels. Conclusions Participants identified multi-level influences of the COVID-19 pandemic and pandemic-related response measures on their drug use behavior patterns and overdose risk. These findings suggest that effective harm reduction during large-scale crises, such as the COVID-19 pandemic, must address several levels of influence concurrently.